SENSORI, KADAR ASAM OKSALAT DAN KALSIUM OKSALAT BUBUR INSTAN TALAS-IKAN CAKALANG YANG DISUPLEMENTASI TEPUNG LABU KUNING [The Sensory, Oxalate Acid and Calcium Oxalate Content of Taro- Skipjack Fish Porridge Instant Supplemented by Pumpkin Flour] - Yulianti Yulianti; Bayu ST Basri (Jurnal Teknologi & Industri Hasil Pertanian, 2020)
The development of taro flour as raw material for instant porridge requires the addition of other constituents to improve the quality of sensory and nutrition. The research aimed to determine the effect of the addition of pumpkin flour to the level of preference and content of oxalic acid and calcium oxalate instant taro-skipjack fish. The study used a Completely Randomized Design with the treatment of 3 concentrations of pumpkin flour (5%, 10%, 15%) applied to taro-skipjack fish-taro flour as an instant porridge material. The results showed that the level of panelists' preference increased with increasing concentrations of pumpkin flour. The treatment of pumpkin flour 15% produced the best sensory instant pulp both in terms of color, taste, aroma, and texture. The content of oxalic acid and calcium oxalate in the treatment was 0.54 mg / 100 g and 2.41 mg / 100 g, respectively.